Pendekatan Filosofis Terhadap Kebahagiaan Dalam Perspektif Al-Qur'an Bagi Manusia Modern - Abullah, Muammar; Muid N., Abd.; Nurbaiti, Nurbaiti (Green Publisher Indonesia, 2025)
Happiness is the main goal in human life, but the concept and how to achieve it are often debated in various perspectives, including philosophy and religion. The Qur'an as a guideline for the life of Muslims provides a comprehensive view of happiness, which is not only limited to material aspects, but also includes spiritual and moral dimensions. This article discusses happiness from the perspective of the Qur'an with a philosophical approach that is relevant to modern humans. This study examines the concept of happiness based on the verses of the Qur'an and the interpretations of scholars, then relates it to the challenges of contemporary life. The results of the study show that true happiness according to the Qur'an lies in peace of mind obtained through faith, good deeds, and gratitude. In addition, the understanding of happiness in Islam cannot be separated from the balance between worldly and hereafter aspects. Thus, a philosophical approach based on the Qur'an can be a solution for modern humans in achieving true and sustainable happiness.